A review study on the anti-trichomonas activities of medicinal plants. (April 2021) - Hashemi, Nooshin; Ommi, Davood; Kheyri, Parya; Khamesipour, Faham; Setzer, William N.; Benchimol, Marlene
Abstract: The parasitic diseases represent the most important health risk, especially in underdeveloped countries where they have a deep impact on public health. Trichomoniasis is a prevalent non-viral sexually transmitted disease, and a significant amount of new cases are identified each year globally. Furthermore, the infection is linked with serious concerns such as pregnancy outcomes, infertility, predisposition to cervical and prostate cancer, and increased transmission and acquisition of HIV. The therapy is restricted, adverse effects are often observed, and resistance to the drugs is emerging. Based on this, a new treatment for trichomoniasis is necessary. Natural products represent a rich source of bioactive compounds, and even today, they are used in the search for new drugs. Additionally, natural products provide a wide variety of leadership structures that can be used by the pharmaceutical industry as a template in the development of new drugs that are more effective and have fewer or no undesirable side effects compared to current treatments. This review focuses on the medicinal plants that possess anti-trichomonal activity in vitro or in vivo . An electronic database search was carried out covering the last three decades, i.e., 1990–2020. The literature search revealed that almost a dozen isolated phytoconstituents are being explored globally for their anti-trichomonal activity. Simultaneously, many countries have their own traditional or folk medicine for trichomoniasis that utilizes their native plants, as a whole, or even extracts. This review focuses mainly on the human parasite Trichomonas vaginalis . However, at some points mention is also made to Tritrichomonas foetus that causes trichomoniasis in animals of high veterinary and economical interest. We will focus on the plants and plant-based compounds and their anti-trichomonal activity. The literature search highlighted that there are abundant compounds that possess anti-trichomonal activity; however, in-depth in-vivo evaluation of compounds and their clinical evaluation has not been undertaken. There is a critical need for new anti-trichomonal compounds, and focused research on phytoconstituents can provide the way forward. Graphical abstract: Image 1